2013
DOI: 10.3390/molecules18022166
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial/Antifungal Activity and Synergistic Interactions between Polyprenols and Other Lipids Isolated from Ginkgo Biloba L. Leaves

Abstract: Polyprenols separated from lipids are promising new components from Ginkgo biloba L. leaves (GBL). In this paper, ginkgo lipids were isolated by extraction with petroleum ether, saponification, and molecular distillation. Eight known compounds: isophytol (1), nerolidol (2), linalool (3), β-sitosterol acetate (4), β-sitosterol (5), stigmasterol (6), ergosterol (7), β-sitosterol-3-O-β-D-glucopyranoside (8) and Ginkgo biloba polyprenols (GBP) were separated from GBL by chromatography and identified mainly by NMR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 27 publications
3
45
0
2
Order By: Relevance
“…The combinations between various components have been tested for synergy. The FIC of 0.25 showed that GBP with isophytol mixture had the strongest synergistic effect against Salmonella enterica among all the three tested strains [56].…”
Section: Synergy Among Herbal Antimicrobialsmentioning
confidence: 99%
“…The combinations between various components have been tested for synergy. The FIC of 0.25 showed that GBP with isophytol mixture had the strongest synergistic effect against Salmonella enterica among all the three tested strains [56].…”
Section: Synergy Among Herbal Antimicrobialsmentioning
confidence: 99%
“…And the fluorescence was collected at 30-second intervals and measured at λ ex = 405 nm and λ em = 418 nm with a Varioskan Flash multimode plate reader (Thermo Fisher Scientific, Finland). The fluorescence is expressed as mean values with standard error of the means (SEM) and analysis of variance (single-factor ANOVA, Tukey's test at 5% probability) [6]. …”
Section: Methodsmentioning
confidence: 99%
“…Here we reported some of them with the aims of justifying and confirming the antimicrobial activity of the major compounds found in our EOs. Tao et al [34] reported that nerolidol, followed by linalool, separated from Ginkgo biloba L. leaf EO showed the highest activity and inhibited the growth of Salmonella enterica, Staphylocococus aureus and Aspergillus niger. Lang and Buchbauer [31] reviewed that nerolidol could inhibit the Gram-positive bacteria, but did not sufficiently harm the Gram-negative bacteria.…”
Section: Variation Of the Chemical Classes Within The Eos Of The Diffmentioning
confidence: 99%